Learning diversity in the Chinese classroom : contexts and practice for students with special needs - Phillipson, Shane N. (Book collections on Project MUSE., 2007)
This work focuses on the special learning needs of the Chinese student. It provides both a theoretical perspective as well as practical examples of inclusive education in the Chinese classroom.